Guest-Host Interactions in Symmetrical Carboxy Heptamethine Cyanine Dyes-Titanium Dioxide Systems: Synthesis, Theoretical Calculations, Aggregation Properties, and Application in Dye-Sensitized Solar Cells - Rodrigo da Costa Duarte; Matheus Costa de Oliveira; Josene Maria Toldo; Paulo Fernando Bruno Gonçalves; Marcos José Leite Santos; Fabiano Severo Rodembusch (International Journal of Photoenergy)
In this work, the role of deoxycholic acid (DCA) as a coadsorbent was investigated in the sensitization of mesoporous TiO2 layers (host) with symmetrical carboxy heptamethine cyanine dyes (guest). Different approaches have been tested, aimed at reducing the H-aggregation and minimizing the competition between cyanine molecules and DCA for active sites of the host, thus improving solar cell efficiency. Heptamethine cyanines containing carboxylic anchoring groups were obtained with good yields. The cyanines present UV-Vis absorption in methanol and dimethylformamide solutions ascribed to fully allowed electronic transitions (1ππ∗), as well as fluorescence emission in the NIR region, with any evidence of aggregations in both ground and excited states. TD-DFT calculations were also performed in order to study the geometry and charge distribution of these compounds in their ground and excited electronic states. Solid-state photophysics indicates that the cyanines showed excellent adsorption on TiO2, which can be justified by the presence of the -COOH moieties in the structure. Photophysical measurements have revealed the best concentrations of dye and DCA, which resulted in efficient inhibition of cyanine H-aggregates on the TiO2 surface in addition to allow large dye loading. HOMO and LUMO energy levels of the dyes were identified by cyclic voltammetry, showing oxidation and reduction potentials within acceptable limits for application as a photosensitizer in dye-sensitized solar cells (DSSCs) based on a TiO2 mesoporous photoanode. Assembled DSSCs have shown a large improvement of the electrical parameters and efficiency when a balance between dye aggregation and the competition to the host active sites was reached.